3d-3d correspondence for mapping tori - Sungbong Chun; Sergei Gukov; Sunghyuk Park; Nikita Sopenko (Journal of High Energy Physics, 2020)
Abstract One of the main challenges in 3d-3d correspondence is that no existent approach offers a complete description of 3d N $$ \mathcal{N} $$ = 2 SCFT T [M 3] — or, rather, a “collection of SCFTs” as we refer to it in the paper — for all types of 3-manifolds that include, for example, a 3-torus, Brieskorn spheres, and hyperbolic surgeries on knots. The goal of this paper is to overcome this challenge by a more systematic study of 3d-3d correspondence that, first of all, does not rely heavily on any geometric structure on M 3 and, secondly, is not limited to a particular supersymmetric partition function of T [M 3]. In particular, we propose to describe such “collection of SCFTs” in terms of 3d N $$ \mathcal{N} $$ = 2 gauge theories with “non-linear matter” fields valued in complex group manifolds. As a result, we are able to recover familiar 3-manifold invariants, such as Turaev torsion and WRT invariants, from twisted indices and half-indices of T [M 3], and propose new tools to compute more recent q-series invariants Z ̂ $$ \hat{Z} $$ (M 3) in the case of manifolds with b 1 > 0. Although we use genus-1 mapping tori as our “case study,” many results and techniques readily apply to more general 3-manifolds, as we illustrate throughout the paper.